Women in Islamic Law: Rights, Responsibilities, and Contemporary Challenges of Implementation - Ominakhon Akhmedjanova (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
The history of women in Islam is studied through Quranic verses, hadiths, and scholarly research on family relations in order to understand the legal status of women. This article examines the status of women in pre-Islamic Arabia and in Islam, as well as their position after the revelation of the Quran, including property rights, mahr, the right to separate residence of spouses, and the interaction between cultural traditions and religious values. The study also discusses contemporary practices that contradict Islamic law, as well as the imposition of duties on women that are not prescribed by Islam. The article concludes that the Islamic legal system was among the first to provide women with comprehensive social and property protection.